Tabula Rasa, Point of View, and the Ideology of Feminism - Mytha Candria (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2020)
This article concerns point of view and the ideology of feminism in Ratih Kumala’s novel Tabula Rasa. Point of view is defined with reference to the angle of telling a narrative, whereas feminism is the belief that women and other minority groups suffer from violence, repression, and discrimination. Here, point of view is analyzed based on three different classifications, i.e. Fowler-Uspensky model, Simpson’s mode of narration or Al-Alami’s types of narrators, and Uspensky’s types of narration. The result suggests that Ratih Kumala uses first and third person points of view and internal type of narration to communicate her support for feminism.